Optimized GMP-grade production of non-viral Sleeping Beauty-generated CARCIK cells for enhanced fitness and clinical scalability - Ilaria Pisani; Giusi Melita; Patricia Borges de Souza; Stefania Galimberti; Angela Maria Savino; Jolanda Sarno; Beatrice Landoni; Stefano Crippa; Elisa Gotti; Carolina Cuofano; Olga Pedrini; Chiara Capelli; et al. (Journal of Translational Medicine)
Abstract Background Strict adherence to GMP guidelines and regulatory compliance is crucial when transitioning from research to clinical-grade production of ATMPs like CAR T cells. The success of CAR T cell therapy in treating hematological malignancies highlights the need for closed or automated systems to ensure quality and efficacy. Recent evidence also suggests that ex vivo culture conditions can significantly impact CAR T cell functionality. Methods We present our optimized methodology for expanding Sleeping Beauty transposon-engineered Chimeric Antigen Receptor-Cytokine-Induced Killer (CARCIK) cells using G-Rex devices and evaluate its impact on CARCIK cell phenotype and T cell fitness. Results Building on our previously validated protocol, we introduced key simplifications to optimize the CARCIK differentiation process. Delaying the nucleofection step eliminated the need for feeder cells while maintaining efficient CAR expression and high cell viability. Transitioning from T-flasks to G-Rex bioreactors reduced operator hands-on time from 21 to 28 days to 14–17 days and resulted in a less differentiated CARCIK cell product. Metabolic and transcriptional analyses showed that the novel protocol improves CARCIK cell fitness and in vivo efficacy against B-cell lymphoma. The novel method was validated in Good Manufacturing Practices (GMP) conditions at our two Cell Factories and yielded enough numbers of CARCIK-CD19 cells for clinical use. Conclusions Optimizing non-viral CARCIK cell production using G-Rex bioreactors and refined timing adjustments has streamlined the workflow, enhanced cell fitness, and resulted in a highly effective therapeutic product with demonstrated in vivo efficacy in mice. These improvements reduced manipulation and contamination risks, while optimizing logistics and space efficiency, facilitating allogeneic CARCIK generation for a current phase I/II clinical trial (NCT05869279) in patients with R/R CD19 + non-Hodgkin Lymphoma (B-cell NHL) and Chronic Lymphocytic Leukemia (CLL), confirming the approach’s scalability and clinical potential.